Etimologies in the American Spanish - Portilla, Mario (2015)
The treatment of etimologies in the American Spanish in regional and general dictionaries shows carelessness and lack of interest by the researchers of Hispanic American lexicography. That is why the etimological research in this area is promising albeit difficult. This article presents an ongoing project about Spanish etimologies in Costa Rica, the first stage of a larger etimological study of Central American Spanish. Finally, this research will contribute to the understanding of etimologies of American Spanish in general.